KATA SERAPAN (GAIRAIGO) PADA MANGA DORAEMON KARYA FUJIKO FUJIO - Fadhila Putri Madya; Arza Aibonotika; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses changes in the meaning of loandwords or gairaigo. The purpose of this study is to explain the changes in meaning that exist in loanwords or gairaigo in Japanese manga or comics. The data in this study is the vocabulary that is considered as loan word in the Manga Doraemon volume 6 by Fujiko Fujio. This is a qualitative research with a descriptive approach. The result of the analysis of Didi Sutedi’s theory found 4 changes in meaning from 33 gairaigo.Key Words: Change in meaning, Gairaigo, Manga Doraemon.